2017
DOI: 10.3748/wjg.v23.i10.1857
|View full text |Cite
|
Sign up to set email alerts
|

Hospital resource intensity and cirrhosis mortality in United States

Abstract: AIMTo determine whether hospital characteristics predict cirrhosis mortality and how much variation in mortality is attributable to hospital differences.METHODSWe used data from the 2005-2011 Nationwide Inpatient Sample and the American Hospital Association Annual survey to identify hospitalizations for decompensated cirrhosis and corresponding facility characteristics. We created hospital-specific risk and reliability-adjusted odds ratios for cirrhosis mortality, and evaluated patient and facility differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
3
18
0
2
Order By: Relevance
“…That said, in a study by Volk et al ,15 proper titration of lactulose and diuretics along with failure to plan out-patient paracenteses were the greatest drivers of “preventable” readmissions. Of interest though, there have been multiple studies that have shown correlation between spending and improved morality, including cirrhosis,16–20 which is in line with this study’s results. However, another study by Fisher et al 21 demonstrated that greater spending driven by more specialists’ involvement and therapeutic interventions were not correlated with improved outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…That said, in a study by Volk et al ,15 proper titration of lactulose and diuretics along with failure to plan out-patient paracenteses were the greatest drivers of “preventable” readmissions. Of interest though, there have been multiple studies that have shown correlation between spending and improved morality, including cirrhosis,16–20 which is in line with this study’s results. However, another study by Fisher et al 21 demonstrated that greater spending driven by more specialists’ involvement and therapeutic interventions were not correlated with improved outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Liver disease severity, as assessed by MELD scores, was similar for the patients of the two hospitals. U1 and U2 were similar with regard to features considered advantageous, 14 including having high volumes of patients with cirrhosis, emergency and intensive care departments, academic hospital status, and advanced endoscopic and radiological facilities.…”
Section: Discussionmentioning
confidence: 90%
“…It is difficult to identify the specific aspect of the multifaceted care model most likely to have contributed to its positive effects, but the dedicated inpatient liver unit, staffed by gastroenterologists with a special interest and experience in hepatology and liver transplantation, may have been important, as specialist care has been associated with reduced mortality among patients with decompensated cirrhosis 15 . The presence of the state liver transplantation unit at U1 may have influenced outcomes, as transplantation centres are associated with lower in‐hospital mortality among patients with cirrhosis 14 . However, patients in U1 and U2 had equal access to the liver transplant facility.…”
Section: Discussionmentioning
confidence: 99%
“…(34,35) Our findings support those of previous studies that demonstrated the importance of hospital-level characteristics to outcomes among patients with cirrhosis. (7,8) Mellinger et al found that patients admitted to rural hospitals had a 27% higher odds of in-hospital mortality than patients admitted to urban hospitals after accounting for patient-level factors. However, in their cohort, this effect was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the treating hospital play a large role in the outcomes of patients with cirrhosis. Inpatient mortality varies substantially among hospitals and is partially attributable to differences in resource intensity at the hospital level . Little is known about treatment outcomes in rural hospitals, where outcomes for other conditions, such as acute myocardial infarction and congestive heart failure, are known to be inferior .…”
mentioning
confidence: 99%